Net radiation during cloudy, damp conditions in the snow-free season at Poste-de-la-Baleine (Great Whale), Québec - Wilson, Cynthia (Cahiers de géographie du Québec, 1972)
In aprevious study, a close linear relationship was indicated between net radiation andincoming solar radiation at Poste-de-la-Baleine, in late May/early June, for damp surfaces of many types, under cool, humid, cloudy conditions. Using the standard hourly weather observations at the AES station for 1969, an attempt is now made to determine to whatextent this relationship may be typical of the entire snow-free season.The results suggest that nearly one half of all daylight hours conformed to these conditions, and that the radiation curve is characteristic of weather associated with onshore winds. Certain ecological implications of this conclusion are noted.